G459(P) Weight-related quality of life of children and adolescents. (27th April 2016) - Al-Hashimi, S; Davis, N; Bull, K
Abstract : Aims: Psychosocial outcomes of obesity in children and adolescents although important are often under-reported and can be difficult to assess and manage. This study looked at the quality of life (QoL) of this cohort in the United Kingdom. It also explored the relationships between QoL and gender, age, ethnicity, socio-economic status, co-morbidities, and schooling. Methods: Participants were recruited from the hospital paediatric endocrinology weight management services. Height, weight, body mass index (BMI), BMI standard deviation score (SDS), and demographic data were collected cross-sectionally and co-morbidities were acquired from patient notes. QoL scores were obtained using two questionnaires: Paediatric Quality of Life Inventory (PedsQL) and Impact of Weight on Quality of Life-Kids (IWQOL-Kids). Data was analysed using Pearson's Correlation, Independent T-test, and One-Way analysis of variance (ANOVA). Results: Twenty-eight patients were recruited; 18 females and 10 males, and the mean (SD) age was 14.6 (2.3) years. The mean (SD) BMI SDS was 3.1 (0.6). The total number of co-morbidities ranged from 0–5, most commonly insulin resistance, 35.7%, and depression, 32.1%. The average total PedsQL score (SD) was 57.2 (21.0), and the lowest sub-scale score was school functioning, scoring 50.6 (26.9). The average total IWQOL-Kids score (SD) was 71.8 (20.3), and the lowest mean sub-scale score was body esteem, scoring 49.2 (31.3). A significant moderate negative correlation was found between BMI SDS and PedsQL emotional functioning ( r =-0.437, p = 0.020) and a significant moderate negative correlation was found between BMI SDS and IWQOL-Kids physical comfort ( rs = −0.385, p = 0.043). Significant moderate negative correlations were found between the number of co-morbidities and PedsQL physical functioning ( r = −0.421, p = 0.026) and between the number of co-morbidities and IWQOL-Kids family relationships ( rs = −0.435, p = 0.021). Children who missed more than 4 days of school in the previous term (N=15) scored a lower PedsQL emotional functioning score, 65.0 (24.9) vs. 46.5 (22.8), (p = 0.05) Conclusion: This study supports existing evidence that the overweight and obese cohort have a reduced QoL, particularly in physical and emotional functioning. It also supports evidence that an increase in the number of co-morbidities reduces QoL. Reduced QoL is also associated with reduced school attendance, with two participants stating bullying had caused them to leave mainstream education.